The Effect of Financial Literacy and Self-Control on Consumptive Behavior with Paylater as a Mediating Variable - Sofiah Nada Fauziah; Putra Hilmi Prayitno; Hari Wahyono; Ro’ufah Inayati (University of Merdeka Malang, 2023)
This study aims to analyze: (1) the effect of financial literacy on consumptive behavior, (2) the effect of self-control on consumptive behavior, (3) the effect of Paylater on consumptive behavior, (4) the effect of financial literacy on Paylater, (5) the effect of self-control on Paylater, (6) Paylater as mediating variable. This research uses quantitative research methods. The number of samples in this study was 100 housewives in Malang. The analysis technique uses SEM PLS. The results of the analysis show: (1) the financial literacy influences consumptive behavior, (2) the self-control influences consumptive behavior, (3) Paylater influences consumptive behavior, (4) financial literacy influences Paylater, (5) self-control affects Paylater, (6)Paylater mediates the effect of financial literacy on consumptive behavior, (7) Paylater mediates the effect of self-control on consumptive behavior in housewives in Malang. Thus, the use of the Paylater feature is only for purchases that are absolutely necessary and within budget. Increase self-control so that you can help avoid the harmful consumptive behavior.